CAR Immunotherapy for the treatment of infectious diseases: a systematic review - Morte-Romea, Elena; Pesini, Cecilia; Pellejero-Sagastizábal, Galadriel; Letona-Giménez, Santiago; Martínez-Lostao, Luis; Aranda, Silvia Loscos; Toyas, Carla; Redrado, Sergio; Dolader-Ballesteros, Elena; Arias, Maykel; Galvez, Eva M.; Sanz-Pamplona, Rebeca; et al. (Frontiers in Immunology, 2024)
Immunotherapy treatments aim to modulate the host’s immune response to either mitigate it in inflammatory/autoimmune disease or enhance it against infection or cancer. Among different immunotherapies reaching clinical application during the last years, chimeric antigen receptor (CAR) immunotherapy has emerged as an effective treatment for cancer where different CAR T cells have already been approved. Yet their use against infectious diseases is an area still relatively poorly explored, albeit with tremendous potential for research and clinical application. Infectious diseases represent a global health challenge, with the escalating threat of antimicrobial resistance underscoring the need for alternative therapeutic approaches. This review aims to systematically evaluate the current applications of CAR immunotherapy in infectious diseases and discuss its potential for future applications. Notably, CAR cell therapies, initially developed for cancer treatment, are gaining recognition as potential remedies for infectious diseases. The review sheds light on significant progress in CAR T cell therapy directed at viral and opportunistic fungal infections.